Keeping the scale from tipping: Bolstering the sustainability of Indonesia’s data center industry development - Manullang, Abel Josafat (Digital Theory, Culture & Society, 2024)
The Indonesian government has demonstrated a keen interest in the digital economy. In order to further reinforce its digital economy, Indonesia has identified the data center industry as a key target for growth. The article employs a qualitative research method to elucidate potential avenues for enhancing the sustainability of Indonesia's data center industry. The article commences with an examination of Indonesia's digital economy potential and its correlation with the data center industry. In light of the projected growth of the digital industry and internet penetration, as evidenced by the 2030 estimates, the necessity for the establishment of data centers is becoming increasingly apparent. Subsequently, an analysis of the industry's financial implications is presented, with a particular focus on its considerable water and electricity consumption and associated greenhouse gas emissions. The aforementioned matter could impact Indonesia's progress in reducing its carbon footprint, not to mention other potential repercussions in numerous sectors. Domestically, Indonesia can pursue sustainable development through engaging with relevant domestic actors and promoting the wider use of renewable energy where it is deemed appropriate and feasible. Finally, with international cooperation, Indonesia can leverage its experience in ASEAN and engage with other states that are poised to develop their own data center industry.